Preclinical evaluation of antimalarial activity of CPF-1 formulation as an alternative choice for the treatment of malaria - Prapaporn Chaniad; Tachpon Techarang; Arisara Phuwajaroanpong; Walaiporn Plirat; Prasit Na-Ek; Atthaphon Konyanee; Parnpen Viriyavejakul; Abdi Wira Septama; Chuchard Punsawad (BMC, 2023)
Abstract Background Kheaw Hom remedy is a traditional Thai medicine used to treat fever. Some plants used in the Kheaw Hom remedy show promising in vitro antimalarial activity. This study prepared novel formulations of plants from the Kheaw Hom remedy and evaluated their antimalarial and toxicological activities. Methods Seven new formulations were prepared by combining at least three herbs of six selected plants from the Kheaw Hom remedy, namely Mammea siamensis Kosterm., Mesua ferrea L., Dracaena loureiroi Gagnep., Pogostemon cablin (Blanco) Benth., Kaempferia galanga L, and Eupatorium stoechadosmum Hance. In vitro antimalarial activities of each formulation's aqueous and ethanolic extracts were evaluated using the parasite lactate dehydrogenase (pLDH) assay. Cytotoxicity in Vero and HepG2 cells was assessed using the MTT assay. An extract with good antimalarial potency and selectivity index (SI) was selected for in vivo antimalarial activity using Peter's 4-day suppressive test and acute oral toxicity test in mice. In addition, bioactive compounds were identified using Gas chromatography-mass spectrometry (GC-MS) analysis. Results Among the seven new formulations, ethanolic extracts of CPF-1 (Formulation 1) showed the highest activity with an IC50 value of 1.32 ± 0.66 µg/ml, followed by ethanolic extracts of Formulation 4 and Formulation 6 with an IC50 value of 1.52 ± 0.28 µg/ml and 2.48 ± 0.34 µg/ml, respectively. The highest SI values were obtained for the ethanolic extract of CPF-1 that was selected to confirm its in vivo antimalarial activity and toxicity. The results demonstrated a significant dose-dependent reduction in parasitemia. Maximum suppressive effect of the extract (72.01%) was observed at the highest dose administered (600 mg/kg). No significant toxicity was observed after the administration of 2000 mg/kg. Using GC-MS analysis, the most abundant compound in the ethanolic extract of CPF-1 was ethyl p-methoxycinnamate (14.32%), followed by 2-propenoic acid, 3-phenyl-, ethyl ester, (E)- (2.50%), and pentadecane (1.85%). Conclusion The ethanolic extract of CPF-1 showed promising in vitro and in vivo antimalarial efficacy, with no toxic effects at a dose of 2000 mg/kg, suggesting that the ethanolic extract of CPF-1 may serves as a new herbal formulation for the treatment of malaria. Additional research is required for safety and clinical pharmacology studies.